Physical Fitness Training and Performance Karate Athletes - Razak, Abraham (Indonesian Journal of Educational Studies, 2013)
This study aims to determine the effect of physical fitness strength training aspect to the achievement of karate athletes. Using a quasi-experimental research method. The population used is the athlete PON XVII in East Kalimantan. Total sample of 16 athletes athletes. The data analysis technique used is a t-test at the 95% significance level. The results showed that; (1) There was a significant effect of physical fitness training aspects of the strength of the results of the athlete's performance karate PON XVII in East Kalimantan in 2008, proved t0 = 4.875> tt = 2.131, (2) There was a significant effect of physical fitness training muscle endurance aspect of the results of achievement karate athletes PON XVII in East Kalimantan in 2008, proved t0 = 9.233> tt = 2.131, and (3) There was a significant effect of physical fitness training aspects of the general resistance against karate athlete's achievements PON XVII in East Kalimantan in 2008, proved t0 = 3.738> tt = 2.131.